2020
DOI: 10.1103/revmodphys.92.011003
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium : Neutrino detectors as tools for nuclear security

Abstract: For over 40 years, physicists have considered possible uses for neutrino detectors in nuclear nonproliferation, arms control, and fissile materials security. Neutrinos are an attractive fission signature because they readily pass through matter. The same property makes neutrinos challenging to detect in systems that would be practical for nuclear security applications. This colloquium presents a broad overview of several potential neutrino applications, including the near-field monitoring of known reactors, fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 120 publications
0
96
0
Order By: Relevance
“…Recent work has shown that neutrino detectors, both using IBD (i.e.ν e capture on free protons) and CEνNS on nuclei, can serve as novel state of the art instruments for monitoring nuclear facilities (see [227] for a review). This includes both civilian nuclear reactors, where precise measurements of theν e flux can provide information about spent fuel [228,229], and the global excess of fissile nuclear materials [230,231].…”
Section: Nuclear Facility Monitoringmentioning
confidence: 99%
“…Recent work has shown that neutrino detectors, both using IBD (i.e.ν e capture on free protons) and CEνNS on nuclei, can serve as novel state of the art instruments for monitoring nuclear facilities (see [227] for a review). This includes both civilian nuclear reactors, where precise measurements of theν e flux can provide information about spent fuel [228,229], and the global excess of fissile nuclear materials [230,231].…”
Section: Nuclear Facility Monitoringmentioning
confidence: 99%
“…There are a significant number of collaborations currently attempting reactor CEvNS detection, including CONUS [11], MINER [12], NUCLEUS [13], RED-100 [14], NEON [15], RICOCHET [16], TEXONO [17], CONNIE [18]. There are numerous goals in basic science related to reactor CEvNS [19][20][21][22][23] as well as the aforementioned potential applications to reactor monitoring for nuclear security [5][6][7][8].…”
Section: IImentioning
confidence: 99%
“…The use of neutrinos for applications in reactor monitoring in a nuclear security context has been widely discussed, for a recent review see Ref. [5] and references therein. The main advantage of neutrinos compared to say, ionizing radiation or neutron signatures, is the fact that they can penetrate arbitrary amounts of material and thus, can "see" into places like the core of a running nuclear reactor which are otherwise inaccessible.…”
Section: Introductionmentioning
confidence: 99%
“…From these considerations it follows immediately that any attempt at monitoring a naval reactor while at full or fractional cruising power would require "drive-by" style monitoring, resulting in a very small product of dwell time and reactor power. This makes online monitoring (when the reactor is operating) of the reactor core via the usual neutrino-based techniques [15][16][17] impractical. Limited dwell time while the reactor is on also precludes the use of more exotic techniques like the observation of breeding neutrinos [18] or non-linear effects related to power density [19].…”
Section: Submarine and Reactor Considerationsmentioning
confidence: 99%